POPULATION DYNAMICS OF A CLADOCERAN ZOOPLANKTER1 DAPHNIA MAGNA, IN TWO POULTRY-CUM-FISH (DUCK-FISH & CHICKEN-FISH) INTEGRATED PONDS.
The population dynamics of Daphnia magna was studied in two integrated fish-cumpoultry ponds (duck-fish and chicken-fish). The seasonal changes in the population of D. magna were recorded. Peak population of the zooplankter was recorded in the month of January in both ponds. The birth rate (b), growth rate (r) and death rate d) of D. magna were studied in field as well as in the laboratory. Three temperatures and three different food concentrations were selected for laboratory study. The maximum values of b) and (r) were recorded during December January in field. Under laboratory conditions, highest birth and death rate occurred at lowest temperature 15 °C). Both food and temperature were found to affect the population dynamics of the species; longest life span and maximum population were recorded at lowest temperature and maximum food concentration. Keywords: Population dynamics, Cladocera, Daphnia magna, Integrated fish -cum -poultry ponds. , journal=Journal of Indian Fisheries Association, author=Arachana, Arachana and Sharma, A. P. and Das, M., year=2009, month=Dec.